Study on Deformation Evolution Characteristics of Reverse-Dip Rock Slope under the Influence of Rainfall - Jiabing Zhang; Liangfu Xie; Xuejun Liu; Yongjun Qin; Liming Wu (Advances in Civil Engineering)
In Southwestern China, there exists deep river valleys and abundant rainfall, which leads to a large number of reverse-dip rock slopes. In order to investigate the evolution characteristics of toppling deformation of reverse-dip slope under the influence of rainfall, and a typical reverse-dip slope was taken as an engineering case. Firstly, the temporal and spatial evolution nephogram of toppling displacement under different rainfall was obtained based on the discrete surface displacement monitoring data of bank slope. Then, taking bank slope, gully buffer zone, and development degree of bank slope as development characteristics based on geological field survey, afterward, the evolution characteristics in different strong deformation zones were analyzed by superimposing the development characteristic partition and the spatial and temporal displacement nephogram. The results showed that the horizontal displacement mainly occurred on the right front and middle rear of the bank slope while large vertical displacement occurred on the middle of the bank slope under the influence of rainfall. As the rainfall increased to the maximum, the toppling deformation reached the peak, and vertical displacement was more sensitive to the rainfall than horizontal displacement. After the superposition, the largest strong deformation zone was located in the middle and rear part of the bank slope, which is characterized by medium and high slope and mature stage and 50 m gully buffer zone. This paper explores the deformation and failure process of reverse-dip rock slope considering the change of rainfall through real displacement monitoring data and focuses on the real deformation evolution law of each characteristic zone combined with different development characteristics partition.